Tuberculosis Case Finding And Diabetes Mellitus Screening In Vulnerable Populations Budi Luhur Nursing Home Jambi - Helmi Suryani Nasution; Rd. Halim (Interest : Jurnal Ilmu Kesehatan, 2021)
Background: Indonesia was ranked third in 2018 for tuberculosis (TB) incidence among other countries in the world. Indonesia is also facing non-communicable diseases (NCDs) and re-emerging disease. One of the NCDs problems in Indonesia is diabetes mellitus. These two diseases are interrelated. The prevalence of TB and diabetes mellitus in the elderly is much higher than in the other age groups. The purpose of this study was to determine the proportion of TB and diabetes mellitus and risk factors associated with each of these diseases in the elderly. Methods: The research was conducted at the Budi Luhur Nursing Home. The number population and sample is 70 people. The research design was cross-sectional. Univariate analysis was shown in the distribution of frequencies and proportions and bivariate analysis was performed using a chi-square test. Results: The proportion of TB was 2.4% while the proportion of diabetes mellitus was 14.6%. History of diabetes mellitus was associated with diabetes mellitus (p-value=0.015 and POR 7.11 (95% CI 1.543 - 32.764)). Age, gender, nutritional status, stress, physical activity, and history of TB were not associated with diabetes mellitus. Conclusion: : It is recommended to conduct other studies with a better design and to consider a research method that is suitable for the elderly.